2021
DOI: 10.1252/jcej.21we009
|View full text |Cite
|
Sign up to set email alerts
|

Sinter-Necked, Mixed Nanoparticles of Metallic Tungsten and Tungsten Oxide Produced in Fuel-Rich Methane/Air Tubular Flames

Abstract: Metallic tungsten nanoparticles have attracted considerable attention because of their unique structures and excellent performances. This paper describes the synthesis of a mixture of tungsten metal and oxide nanoparticles via a fuel-rich tubular ame process, followed by mild-reduction-based post-heating treatment. The high combustion e ciency of the tubular ame process enables complete consumption of O 2 in the premixture, along with the emission of CO and H 2 . The experimental results revealed that the tubu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The flame aerosol process offers the advantages of a single-step and continuous process, less time-consuming, a large temperature gradient, and high productivity. 40−43 This method allows synthesizing high-purity metal oxide nanoparticles with unique morphologies, 43−45 such as chain-like structures, 46 close-packed aggregated network structures, 46 necking structures, 40,41,46,47 and fused-aggregated network structures. 40,48 These network structures of particles improve the conductivity and reduce the amount of usage of precious metals such as Pt, Ir, and Nb.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The flame aerosol process offers the advantages of a single-step and continuous process, less time-consuming, a large temperature gradient, and high productivity. 40−43 This method allows synthesizing high-purity metal oxide nanoparticles with unique morphologies, 43−45 such as chain-like structures, 46 close-packed aggregated network structures, 46 necking structures, 40,41,46,47 and fused-aggregated network structures. 40,48 These network structures of particles improve the conductivity and reduce the amount of usage of precious metals such as Pt, Ir, and Nb.…”
Section: Introductionmentioning
confidence: 99%
“…The flame aerosol process is a simple and versatile method for synthesizing nanostructured particles in the gas phase with a high production rate from the laboratory to the industrial scale. It can also be used for the production of metal-loaded metal oxide particles. The flame aerosol process offers the advantages of a single-step and continuous process, less time-consuming, a large temperature gradient, and high productivity. This method allows synthesizing high-purity metal oxide nanoparticles with unique morphologies, such as chain-like structures, close-packed aggregated network structures, necking structures, ,,, and fused-aggregated network structures. , These network structures of particles improve the conductivity and reduce the amount of usage of precious metals such as Pt, Ir, and Nb. Furthermore, the flame aerosol process can be used to synthesize metal-loaded metal oxide particles with low concentrations of precious metals.…”
Section: Introductionmentioning
confidence: 99%
“…Nb-doped tin oxide (Nb–SnO 2 : NTO) has also been developed as a catalyst support for PEFCs, and it exhibits both high electrochemical activity and high durability. In most cases, a flame process is used to produce Nb–SnO 2 nanoparticles. In such a process, the raw precursor material is introduced into a flame in a gas phase to obtain fine particles. The structures of flame-made fine particles can be controlled precisely by adjusting the type of solvent and by changing the combustion method. Using this method, Nb–SnO 2 nanoparticles have been synthesized in a network structure in which the particles are fused together, and this material has been used as an electrocatalyst. For example, Kakinuma et al have reported the synthesis of NTO nanoparticles and their application as catalyst supports for PEFC cathodes with improved durability .…”
Section: Introductionmentioning
confidence: 99%